Beyond aerodigestion: Exaptation of feeding-related mouth movements for social communication in human and nonhuman primates. (13th December 2017) - Murray, Lynne; Sclafani, Valentina; Rayson, Holly; De Pascalis, Leonardo; Bozicevic, Laura; Ferrari, Pier Francesco
Abstract: Three arguments are advanced from human and nonhuman primate infancy research for the exaptation of ingestive mouth movements (tongue protrusion and lip smacking) for the purposes of social communication: their relation to affiliative behaviours, their sensitivity to social context, and their role in social development. Although these behaviours may have an aerodigestive function, such an account of their occurrence is only partial.